Leading Role of the Principles of Interaction between the Natural Physical Factors and Integral Organism in Medecine of the Future (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: physiodynamics; physiokinetics; supramolecular structures; blood spectrum biopsy